‘From theatre and music’. Functions and tasks of opera criticism in selected Warsaw periodicals of the second half of the 19th century - Kaminiczna, Natalia (Interdisciplinary Studies in Musicology, 2026)
The article analyses the emergence and development of press opera criticism in Warsaw in the second half of the nineteenth century, viewing it as a phenomenon situated at the intersection of theatrical and musical criticism. It begins by pointing to underdeveloped research tradition in the field of opera criticism and the lack of established terminology, which complicate scholarly description of this area. The aim of the article is to present press opera criticism as an important supplement to the history of the Polish operatic stage. As a reflection of audience tastes, this form of criticism simultaneously helped to shape them, exerting influence through specific writing and rhetorical strategies.The analysis focuses on selected periodicals, primarily Bluszcz and Gazeta Muzyczna i Teatralna, with references to Kurier Warszawski and Kurier Codzienny. A comparison of various forms of journalistic expression (brief notices, notes, reviews, and surveys) makes it possible to capture the tension between reportorial criticism, governed by the logic of the chronicle, and „reasoned” criticism, grounded in specialist knowledge and educational ambitions. The article demonstrates that, despite the dispersed nature of the material, opera criticism from the years 1865–1914 constitutes a significant–though still insufficientlyexamined–component of nineteenth-century musical and theatrical culture.